The Influence of Organizational Citizenship Behavior, Work Environment and Knowledge Sharing on Employee Performance - Irvan Nofrandy; Alizar Hasan; Desto Jumeno (Dinasti Publisher, 2025)
In improving employee’s performance, some variables are needed and must exist in employee’s character and environment. Organizational citizenship behavior (OCB), work environment and knowledge sharing are some of that variable mention it. In a government, certainly the employee performance is needed to achieving the main function of government namely service and implementing public policy. Therefore, an empirical study is needed on the effect of some of the variables mentioned on performance for improvement in the government itself. This research aims to find out what variables affect employee performance, along with the dimensions of each variable that affect performance. By continuing to apply the results of the research so that employee performance can be maximized. This research was conducted at government, namely Dinas Perindustrian dan Perdagangan Sumatera Barat Province, with using questionnaire to sample with 75 respondents. The data will process using SEM-PLS which is calculated by SmartPLS 4.0 application. The results showed that OCB had a positive and significant effect together with all of its dimensions except conscientiousness on employee performance. Meanwhile, the work environment dan knowledge sharing have no positive and significant effect. This shows that there needs to be a lot of application and improvement of OCB in order to improve the perfomance of Disperindag employees.